ISLAMIC WEB COMICS AS VISUAL AID IN TEACHING ENGLISH FOR ISLAMIC SECONDARY SCHOOL STUDENTS - Anni Widayanti; Muntaha Muntaha (Indonesian Journal of Islamic Literature and Muslim Society, 2018)
The rise of technology has influenced the education field much. It creates the popularity of online material which can help students in the teaching and learning process. One of it is a web comic, a comic or cartoon published on the internet for everyone to view can be a unique gateway medium to explore visual narrative or story. It is one of the online materials which can attract students especially teenager to read and comprehend the message without feeling bored and realize that they study English. This study aimed to find out whether using Islamic Web Comics is effective in teaching English especially reading comprehension at Islamic secondary school in the Indonesian context. This study is a quasi-experimental with pretest and posttest design; two homogenous groups were selected as experimental and control group. Descriptive analysis and Independent t-test were used for analyzing the data obtained. The result showed that the mean score of the post-test score of the experimental class was 70.88 and control class was 64.69. It was obtained that t-test result was 2.26 higher (2.26 >1.99). It means Islamic Web Comics as visual aid was more effective in teaching English especially reading comprehensions than animated video presentation.